The Development of digital tourism at the Tebing Tegallinggah temple tourist attraction in Bedulu Village, Gianyar Regency, Bali - I Wayan Wiwin; I Made Arsa Wiguna; I Gusti Ketut Indra Pranata Darma; Putu Sabda Jayendra (Universitas Merdeka Malang, 2024)
Candi Tebing Tegallinggah is a tourist attraction located in Bedulu Village, Blahbatuh District, Gianyar Regency. Since it opened as a tourist attraction at the end of 2019, the level of tourist visits to Candi Tebing Tegallinggah is still relatively low, this is because access to information regarding the existence of Tebing TegallinggahÂ especially through online media is still very minimal. Story posts and reviews on social media regarding the existence of the Candi Tebing Tegallinggah are still very minimal, until March 2023 there were only 11 story posts and 26 reviews. Therefore, this research is very important to carry out to create a digital tourism website application in the development of the Candi Tebing Tegallinggah. Data collection in this research was carried out using in-depth interviews, observation, and document study methods. The data was analyzed descriptively and qualitatively using the digital tourism concept approach, the concept of potential tourist attractions, the concept of destination development, and the social action theory approach. The results of this research show that the potential tourist attraction of Tebing Tegallinggah is in the form of natural potential, cultural potential, and artificial potential. The digital tourism application for the Candi Tebing Tegallinggah tourist attraction takes the form of a website (https://canditebingtegallingah.id) which contains information regarding the location, history, and general description of the Candi Tebing Tegallinggah which contains virtual tour content. The development of Candi Tebing Tegallinggah as a tourist attraction has had a positive impact on the economy, socio-culture, and the surrounding environment. The application of digital tourism applications in developing the Candi Tebing Tegallinggah is expected to increase the number of tourist visits.